Implementasi Teknologi Wireless Mesh untuk Jaringan Komunikasi Data pada Wireless Weather Station - Ferdian Yunazar (INKOM Journal, 2012)
To wider the coverage area of a weather sensor and to be always connected in realtime manner with other sensor, we proposed the enhancement of WWS communication data using Multipoint to Multipoint link which is Wireless Mesh Networking. From previous research has resulted a communication data between server and weather sensor using Point to Point link. Wireless mesh as one of variant innovation from WLANs technology offers a unique solution because it could be a replacement or enhancement for the established wireless network to be more effective and efficient. It has a wider coverage area without neglect of security factor and mobility. The result of this research is a Wireless Weather Station system which has been integrated with Mesh Network technology.